ANALISIS KOMPARATIF KINERJA KEUANGAN PT INDOFOOD SUKSES MAKMUR TBK DAN PT GARUDAFOOD PUTRA PUTRI JAYA TBK PERIODE 2017 - 2022 - A.A. Sagung Istri Pramanaswari (Jurnal Ilmiah Global Education, 2023)
This study aims to compare the financial performance of PT Indofood Sukses Makmur TBk and PT Garudafood Putra Putri Jaya TBk in 2017 to 2022, in terms of Current Ratio, Quick Ratio, Cash Ratio, Net profit margin and Return on equity. Data is obtained through financial reports reported on the Indonesia Stock Exchange via the https://www.idx.co.id/ page. The results showed that in the liquidity aspect there was a significant difference in the financial performance of PT Indofood Sukses Makmur TBk and PT Garudafood Putra Putri Jaya TBk, namely the cash ratio indicator. Meanwhile, there is no significant difference in the current ratio and quick ratio indicators. In addition, there is no significant difference in the aspect of profitability of the two companies; this can be seen from the calculation results which show a significance value greater than the value of 0.5. However, based on the results of a comparison using industry average standards, it is known that PT Indofood Sukses Makmur Tbk has a better ability to pay company obligations than PT Garudafood Putra Putri Jaya Tbk.